Sarcoidosis simulating metastasis in patient with Merkel cell carcinoma - Nathália Bordeira Chagas; Lucimar Retto da Silva de Avó; Victor Hugo Maion; Michel Antonio Kiyota Moutinho; Débora Gusmão Melo; Carla Maria Ramos Germano (Sociedade Brasileira de Patologia Clínica, 2014)
Merkel cell carcinoma (MCC) is a rare and aggressive skin neuroendocrine tumor whose etiology remains little known. The immune system dysfunction is considered one of the possible causes, shared with other diseases, like sarcoidosis. This article presents the case of a male patient, in the seventh decade of life, which had a prior MCC diagnosis and was subsequently diagnosed with sarcoidosis, which radiologically simulated lung and mediastinum metastasis. The association between MCC and sarcoidosis is infrequent and rarely described in literature, found in only two case reports.